Promoting IPR Policy and Enforcement in China Summary of Dialogues between OECD and China - Zhang, Gang (OECD Publishing, 2005)
Intellectual property rights (IPRs) have an important role to play in helping China realise a modernisation strategy based on technological upgrading and integration into the global economy. Through the protection they offer to inventors, IPR regimes can help promote domestic technological innovation and facilitate transfer of foreign technology. Having recognised the importance of IPRs, the Chinese government has taken great strides in the past two decades to develop a modern system of IPR legislation and to further amend it in accordance with China's membership in the World Trade Organisation (WTO). Progress with respect to IPR enforcement, however, still falls short of the levels needed to stimulate Chinese innovation and meet the expectations of the international business community. This report summarises two policy dialogues that the OECD organised with China in Spring 2004 on IPR issues. These dialogues aimed at assisting China in its efforts to further improve IPR ...
Keywords: Science and Technology; China, People's Republic